La educación cívica en el compromiso ciudadano en jóvenes de educación secundaria de la Institución Educativa Rogelio Nanantai Shijam U.G.E.L. Alto Amazonas, San Lorenzo 2024 - Juag Tan, Jaure (2025)
The objective was: To verify the extent to which attitudes towards civic education improve civic engagement in secondary school students of the educational institution Rogelio Nanantai Shijam of the U.G.E.L. Alto Amazonas - San Lorenzo 2025. The question was: To what extent do attitudes towards civic education improve civic engagement in high school students? Using a quantitative pre-experimental approach, with a single group Pre-test Post-test of a Population of 88, 36 enrolled were extracted. In the descriptive analysis before and after the intervention. Initially, almost all participants were at the “Insufficient” level. After the intervention, an increase in the “Adequate” and “Optimal” levels is observed. In the inferential analysis the value is < 0.05, so there is no normal distribution. The testing of the hypothesis was nonparametric of ranks with Wilcoxon sign for paired or related samples at a significance level = Alpha = 0.05 = 5%. The test statistic is standardized Z to contrast related or paired samples the Zc Statistic Value is equal to -5.238, p-value = 0.001 = 0.0% and at an error level of 0.000% the citizen commitment improves in all its dimensions: Participation in community activities, Social and environmental responsibility and Knowledge and defense of human rights it is concluded that at a confidence level of 95% the research hypothesis: Attitudes towards civic education significantly improve civic engagement in high school students of the Rogelio Nanantai Shijam educational institution of the U.G.E.L. Alto Amazonas - San Lorenzo 2025.